Pengaruh Kompensasi Terhadap Motivasi Kerja Guru Pada SMP AL- AMIN Pamijahan Bogor - Abidin, Zaenal; Sofyan, Ahmad; Supriyatin (Edusifa: Jurnal Pendidikan Islam, 2023)
This study aims to determine the effect of remuneration on teacher motivation at Al Amin High School, Pamijahan District, Bogor District. The research method used was an inferential type of research with a quantitative approach, with the subjects of the study being teachers of Al-Amin High School and the respondents of this study were all teachers of Al-Amin High School. Sampling was carried out using the method of probabilistic sampling, namely using a saturated sample. Data collection by questionnaire method. The data analyzes used in this study are descriptive respondent analysis, descriptive statistical analysis of variables, hypothesis testing using normality test, homogeneity and hypothesis testing using simple linear regression analysis and t-test. The results of the study, processed with the computer program SPSS version 16.0 for Windows, showed that the r2 value was 0.477, which means that 47.7% of charismatic leadership affects the work ethic of teachers in the Modern Man Ana Islamic boarding school, and the remaining 52, 3% influence of other factors not included in this study. The results of hypothesis testing using a simple linear regression analysis show that compensation affects the motivation of teachers at Al-Amin High School, Pamijahan District, Bogor. The results showed that the value of the beta coefficient (β) was 0.812, indicating that the compensation had a positive effect on the motivation of teachers at Al Amin High School, Pamijahan District, Bogor District. The contribution of the compensation effect to the work motivation of teachers is (∆R2) 0.477 or 47.7%; this shows a significant effect, so this study was able to prove the hypothesis. The value of the regression coefficient of 0.812 indicates that with an increase in compensation by 0.812; teacher's work motivation increased by 0.812; tcount of 4.576 > ttable 2.068, so we can conclude that the compensation variable (X) affects the teacher's work motivation (Y) Compensation has a significant impact on teacher motivation. Thus, this study responds to the proposed hypothesis that compensation has a positive and significant effect on the motivation of teachers at Al Amin High School, Pamijahan District, Bogor District. Key words: remuneration, teacher's work motivation.